DESKRIPSI KEMAMPUAN REPRESENTASI MATEMATIS SISWA PADA MATERI HIMPUNAN DI KELAS VIII SMP - Wati, Widya; Yani T, Ahmad; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstrackThis research aims to the discribe students mathematical representation ability of student in complilation in class VIII SMPI Hunsul Yaqin Pontanak. The method that was use in this research is desciptive methode with survey research. The subject of this research are 31 students. The instrument ofÂ data collecting are written test toÂ in the essay and interview as the follow-up acitivity. The result of data analysis show that the mathematical representation abality of the student with visual learning style have precentage of reach 96,77% and it was categorized as high. The mathematical representation of the students with verbal leraning style have a percentage of reach 66,12% and it was categorized as medium. The mathematical representation of the students with symbolic leraning style have a percentage of reach 53,22% and it was categorized as medium. Keywords : Descrption, Mathematical Representation Ability, Set